Psychological distress due to academic stress among clinical students in a Nigerian tertiary institution - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:Studies of psychological distress among university students identified academic stress as highest in medical students followed by allied-health students and least in those not in any of these two disciplines. The immediate antecedents include poor academic performance, substance abuse, and subsequent drop out. Future impacts as burnouts and poor services delivery can be exorbitant. This study therefore aimed to document the prevalence of psychological distress among two groups of clinical students of College of Medicine, Bayero University Kano. And also report influence of demographics, resilience and social support on the observed prevalence.Methodology:The participants were 122 clinical students from two departments of clinical sciences that is, medicine and physiotherapy. All gave consent before administration of the study instruments consisting of sociodemograhic questionnaire, Hospital Anxiety Depression Scale (HADS), Resilience Scale (RS) and Oslo Social Support Scale (OSS-3).Results:Overall, 63.1% of participants were males while 57.4% were females. The mean age of medical versus physiotherapy students are respectively 22.47 years and 22.17 years. Psychological distress as measured by HADS is higher in medical students (depression [57.4%] and anxiety [61.6%]) compared to physiotherapy students (depression [42.6%] and anxiety [38.4%]). Physiotherapy students had higher resilience and lower social support compared to medical students. The participants’ mean scores on HADS, RS, and OSS-3 is only statistically significant for the RS.Conclusion:It was noted that psychological distress due to academic stress is more among Medical students compared to physiotherapy students. Interventions strengthening social support and improving resilience should be included as part of students’ training.